Development of Etno-STEM Integrated Bioentrepreneur Electronic LKPD PjBL on Technology Innovation Material to Improve Creative Thinking Abilities and Entrepreneurial Interests of High School Students - Ilham Subari; Ixsora Sartika Mercuriani (Jurnal Penelitian Pendidikan IPA, 2024)
This development research aims to produce an ethno-STEM integrated PjBL bioentrepreneur electronic worksheet that is feasible, practical and effective for use in improving creative thinking abilities and entrepreneurial interest. This type of research is Research and Development R&D with the ADDIE model (Analysis, Design, Development, Implement, and Evaluate). The subjects in this research were expert lecturers, teachers and students. The instruments in this research are interview instruments, needs questionnaires, feasibility questionnaires, practicality questionnaires, learning implementation sheets, teaching module validation questionnaires, test instruments, and entrepreneurial interest questionnaires. The instrument will be validated by experts and then tested. Data analysis using Manova and N-gain score tests. The results of this research show that the ethno-STEM integrated bioentrepreneur PjBL electronic worksheet is very feasible with a feasibility score for material experts of 84% and media experts of 94%, very practical with a practicality score for teachers of 100% and students of 89%, and effective as seen from The N-gain test value for creative thinking ability for the experimental class was 0.57 and the control class was 0.47 in the medium category and the N-gain test for entrepreneurial interest in the experimental class was 0.40 and the control class was 0.30 in the medium category. The Manova test obtained sig. hotteling's trace 0.00 < 0.05. The results of the Manova and N-gain tests show that the ethno-STEM integrated bioentrepreneur PjBL electronic LKPD is effective in increasing creative thinking abilities and entrepreneurial interest